Photobiomodulation Therapy Restores IL-10 Secretion in a Murine Model of Chronic Asthma: Relevance to the Population of CD4+CD25+Foxp3+ Cells in Lung - de Brito, Aurileia Aparecida; Gonçalves Santos, Tawany; Herculano, Karine Zanella; Estefano-Alves, Cintia; de Alvarenga Nascimento, Cristiano Rodrigo; Rigonato-Oliveira, Nicole Cristine; Chavantes, Maria Cristina; Aimbire, Flávio; da Palma, Renata Kelly; Ligeiro de Oliveira, Ana Paula (Frontiers in Immunology, 2022)
It is largely known that photobiomodulation (PBM) has beneficial effects on allergic pulmonary inflammation. Our previous study showed an anti-inflammatory effect of the PBM in an acute experimental model of asthma, and we see that this mechanism is partly dependent on IL-10. However, it remains unclear whether the activation of regulatory T cells is mediated by PBM in a chronic experimental model of asthma. In this sense, the objective of this study was to verify the anti-inflammatory role of the PBM in the pulmonary inflammatory response in a chronic experimental asthma model. The protocol used for asthma induction was the administration of OVA subcutaneously (days 0 and 14) and intranasally (3 times/week, for 5 weeks). On day 50, the animals were sacrificed for the evaluation of the different parameters. The PBM used was the diode, with a wavelength of 660 nm, a power of 100 mW, and 5 J for 50 s/point, in three different application points. Our results showed that PBM decreases macrophages, neutrophils, and lymphocytes in the bronchoalveolar lavage fluid (BALF). Moreover, PBM decreased the release of cytokines by the lung, mucus, and collagen in the airways and pulmonary mechanics. When we analyzed the percentage of Treg cells in the group irradiated with laser, we verified an increase in these cells, as well as the release of IL-10 in the BALF. Therefore, we conclude that the use of PBM therapy in chronic airway inflammation attenuated the inflammatory process, as well as the pulmonary functional and structural parameters, probably due to an increase in Treg cells.